Pemasaran Layanan Informasi Perpustakaan di Dinas Perpustakaan dan Kearsipan Kota Medan - Fazria Meiliza Samosir; Anang Anas Azhar; M. Nasihudin Ali (IAI Nasional Laa Roiba Bogor, 2025)
This study examines the marketing of information services at the Library and Archives Office of Medan City. Marketing library services is crucial for increasing public interest in utilizing library facilities. The purpose of this study is to identify the marketing programs implemented by the library, analyze the challenges encountered during the marketing process, and find solutions to overcome these challenges. The method used is descriptive qualitative, with data collection through interviews, observations, and documentation. The results of the study indicate that the library has undertaken several marketing efforts through brochures, the e-Pusda Kota Medan application, and social media. However, the library faces challenges such as limited human resources and budget constraints. As a solution, the library has conducted training for librarians and optimized the available budget. This study is expected to serve as a reference for developing more effective library marketing strategies in the future.